2000
DOI: 10.1075/dia.17.1.04kon
|View full text |Cite
|
Sign up to set email alerts
|

The development of complex reflexives and intensifiers in English

Abstract: SUMMARY Based on some well-established insights into the historical development of English and on a broad typological survey of the relevant domain, an analysis of the development of reflexive anaphors is provided, which raises and answers a number of new questions. The traditional assumption that reflexive anaphors in English developed as a result of combining personal pronouns with the intensifier self is put on solid foundations by a semantic analysis of intensifiers which makes such a development plausi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…As will be shown further below, the new reflexive self-forms showed the same behaviour (see, König and Siemund, 2000, van Gelderen, 2000and Keenan, 2003 for the development of reflexive pronouns). Even as late as in Shakespearean times reflexive anaphors were able to fulfil this double function.…”
Section: The Early Development Of Each Othermentioning
confidence: 90%
“…As will be shown further below, the new reflexive self-forms showed the same behaviour (see, König and Siemund, 2000, van Gelderen, 2000and Keenan, 2003 for the development of reflexive pronouns). Even as late as in Shakespearean times reflexive anaphors were able to fulfil this double function.…”
Section: The Early Development Of Each Othermentioning
confidence: 90%
“…And it becomes more and more clear that an analysis of reflexivity cannot be complete without the semantic point of view. This gap was filled by König & Siemund (2000a, 2000b, 2000c, focusing on the semantics of reflexives and distinguishing reflexivity from intensification. In König & Vezzosi (2002), and many other studies (van Gelderen 2000) the historical development of reflexive pronouns is analyzed in detail.…”
Section: A Brief Summary Of the Theoretical Discussionmentioning
confidence: 99%
“…Apart from the properties mentioned above, former investigations have also revealed that reflexive pronouns and intensifiers exhibit 'a close semantic relatedness' 37 (König & Gast, 2002a): Gelderen, 2000;König & Siemund 2000b;Keenan, 2001).…”
Section: Relationship Between Intensifiers and Reflexive Pronounsmentioning
confidence: 99%
“…Faltz 1985;Levinson 1987Levinson , 1991Kemmer 1993;König and Siemund 2000a;Heine 2003). As has been mentioned in section 1, the historical development of English shows how reflexive markers can arise from adding an intensifier to an otherwise referentially unspecific object pronoun.…”
mentioning
confidence: 98%